2020
DOI: 10.1111/1750-3841.15491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inulin on rheological, textural, and structural properties of brown wheat flour dough and in vitro digestibility of developed Arabic bread

Abstract: The brown wheat flour (BWF)‐based Arabic bread was fortified with chicory‐derived inulin. The objective of this work was to assess the influence of the inulin concentration (1.25 to 5%) on the rheological, textural properties, and fermentation efficacy of enriched BWF dough. Farinographic measurement established that only 3.75% BWF can be substituted by inulin in a dough formulation, which resulted in lowering the water absorption capacity. The peak gelatinization temperature, Tp detected at 74.4 °C by rheomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Table 1 presents the effect of inulin with different properties on water absorption of different pieces of bread investigated in previous studies. According to the previous research, the addition of inulin reduces the water absorption and moisture of the dough, as inulin creates a structure with low elasticity and high viscosity, by weakening the gluten network and at the same time forming areas of high water inclusion capacity (Ahmed et al, 2020 ; Mohammadi et al, 2021 ). Therefore, less water is needed to achieve a dough with the desired consistency.…”
Section: Technological Characteristics Of Bread Containing Inulinmentioning
confidence: 99%
“…Table 1 presents the effect of inulin with different properties on water absorption of different pieces of bread investigated in previous studies. According to the previous research, the addition of inulin reduces the water absorption and moisture of the dough, as inulin creates a structure with low elasticity and high viscosity, by weakening the gluten network and at the same time forming areas of high water inclusion capacity (Ahmed et al, 2020 ; Mohammadi et al, 2021 ). Therefore, less water is needed to achieve a dough with the desired consistency.…”
Section: Technological Characteristics Of Bread Containing Inulinmentioning
confidence: 99%
“…It has been claimed that IN and PD influence the textural properties and sheetability in dough systems ( Ahmed, Thomas, & Khashawi, 2020 ; Samakradhamrongthai, Maneechot, Wangpankhajorn, Jannu, & Renaldi, 2022 ); therefore, understanding this impact is relevant. Table 2 presents the textural parameters and moisture changes in the starchy matrices with and without IN and PD before and after baking.…”
Section: Resultsmentioning
confidence: 99%
“…3). Previous studies have demonstrated that inulin could enhance the gluten network and reduce the collapse of the dough during storage and this most likely played a role in our experiments (Ahmed et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that inulin could enhance the gluten network and reduce the collapse of the dough during storage and this most likely played a role in our experiments (Ahmed et al, 2020). We also examined the slice structure of bread that was generated from our frozen dough samples.…”
Section: Effect Of Inulin On the Specific Volume And Slice Structure ...mentioning
confidence: 98%